2017
DOI: 10.1002/ccr3.1285
|View full text |Cite
|
Sign up to set email alerts
|

The first antenatal diagnosis of KBG syndrome: a microdeletion at chromosome 16q24.2q24.3 containing multiple genes including ANKRD11 associated with the disorder

Abstract: Key Clinical MessageThe loss of ANKRD11 gene confirms the diagnosis of KBG syndrome but does not elucidate the pediatric phenotype providing a counseling challenge. With the expansion of prenatal diagnosis, and the potential to perform whole‐exome sequencing antenatally, we must describe the genetic abnormalities, antenatal ultrasound findings, and phenotype concurrently to facilitate counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The increased rates of perinatal complications in a cohort of individuals with KBG syndrome suggests that there may be an association between ANKRD11 mutations and adverse outcomes in fetuses and newborns. The cardiac deficits and small gestational age findings are consistent with past reports; 11,29 however, the other findings presented here have not been previously documented.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The increased rates of perinatal complications in a cohort of individuals with KBG syndrome suggests that there may be an association between ANKRD11 mutations and adverse outcomes in fetuses and newborns. The cardiac deficits and small gestational age findings are consistent with past reports; 11,29 however, the other findings presented here have not been previously documented.…”
Section: Discussionsupporting
confidence: 92%
“…Limitations aside, this study further documents prenatal and neonatal phenotypes of KBG syndrome. There is one documented case of prenatal confirmation of KBG syndrome, in which a chromosomal microassay (CMA) demonstrated a fetus with a deletion of chromosome 16, including ANKRD11 11 ; however, more studies are needed to further elucidate the prenatal and neonatal phenotypes of KBG syndrome to create more targeted screening measures. More often than not, individuals with KBG syndrome are misdiagnosed or undiagnosed until later in life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All babies reached a gestation age of at least 36 weeks, and the vast majority were delivered at term. In 2017, Victoria Hodgetts Morton et al 4 reported a case of KBGS in a fetus with a 16q24.3 microdeletion that was prenatally diagnosed due to enhanced intestinal echogenicity, but the autopsy revealed a more severe phenotype: triangular face pattern, hypoplastic ears, cryptorchidism, and pulmonary dysplasia. Novara et al 7 compared the phenotypes of KBGS with ANKRD11 mutation and KBGS with 16q24.3 microdeletion and found that KGBS with 16q24.3 microdeletion had a more severe phenotype.…”
Section: Discussionmentioning
confidence: 99%